Machine learning approach for face recognition from 3D models generated by multiple 2D angular images - Mahmud, Moinuddin; Mehzabin, Shegufta; Prova, Sabrina Jahan (Brac University, 2019)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.